The triumph of the antebellum free trade movement - Belko, W. Stephen, 1967- (University Press of Florida, 2012)
In the wake of the War of 1812, the Madison and Monroe administrations oversaw the institution of a series of protective tariffs meant to shield fledgling American industries from British product "dumping." While southerners supported these protectionist measures early on, they quickly came to disapprove of them as severe impediments to trade with the West Indies, an important source of sugar cane and tobacco. In the decades that followed, tariffs became a hotly contested issue, the North favoring protectionism and the South advocating for free trade. In The Triumph of the Antebellum Free Tr.